Anti-racist reorientations to land through gardening with newcomer youth of color - Lognon, Riann; Khandelwal, Chetna; Sanyal, Megha; Dutta, Santanu; Banerjee, Pallavi; Sengupta, Pratim (Frontiers in Climate, 2025)
Our paper seeks to dis/orient normative scholarship on climate migration and climate refugees that reify misleading claims about the relationship between mass migration and climate change, which have been shown to further marginalization of people from the Global South. We orient our attention to a topic that has received considerably less attention in the literature on critical environmental studies: how newcomer (refugee) youth of color (re)establish relationships with more-than-human life, land, air, and water in their newly adopted home in the Global North. Drawing from a three-year-long, community gardening project co-created with the youth, we offer a qualitative analysis of the youths’ participatory, embodied, and discursive work over the first 2 years of creating and caring for the community garden. From a pragmatic perspective, our work arises from the concern that families and youth of color in North America are intersectionally disadvantaged in terms of accessing city resources and public spaces during their resettlement, as noted by critical sociologists of race, migration and gender. Our study reveals how the youths’ participation was centered in the garden through adopting an anti-racist praxis, while also offering an expansive vision of how race and climate are implicated in migration.